The carpool detectives : a true story of four moms, two bodies, and one mysterious cold case - Hogan, Chuck (Random House, 2025)
"In 2020, four women found themselves at a crossroads: Each of them had transitioned from full-time jobs to full-time parenting, and each was pushing against the new boundaries of her life as the pandemic looms. At a bowling night fundraiser for their kids' school, they discover they all share a passion for true crime that crystalizes around a mysterious double homicide that took place a decade earlier. A married couple in their 60s vanished overnight from their home. A few days later, the family business was shuttered, and the bank financing it sued the missing couple for one million dollars. They were rumored to have absconded with the money until their bodies were discovered inside their car at the bottom of a steep ravine. And then the case went cold. But what if, the moms think, they could solve it? The women have no prior connection to the case and no law-enforcement background, but each brings a special set of skills to the investigation: Marissa's background as a former forensic accountant; Jeannie's passion for journalism; Samira's ambition and drive; and Nicole's nose for research. With the world now on pause due to the pandemic, the moms have unique access to witnesses and crime experts who are stuck at home. They make connections, draw conclusions, and experience breakthroughs in the case wilder than anything they could have imagined. When an awe-struck Assistant District Attorney reopens the case, enlisting the four women in the official investigation, they not only get further than anyone ever expected, but end up in real danger themselves"-- Provided by publisher.